2000
DOI: 10.1159/000048385
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Neurotoxin Damage of 6-OHDA to Dopaminergic Nigral Neuron by Subthalamic Nucleus Lesions

Abstract: Object: To investigate the possibility that subthalamic nucleus (STN) ablation could prevent the toxicity of the selective dopaminergic neurotoxin 6-hydroxydopamine (6-OHDA). Methods: Sixty rats were divided into 6 groups (n = 10). The control group received a unilateral microinjection of 6-OHDA into the right ventral tegmental area (VTA) and the right median forebrain bundle (MFB). Group 1 received an administration of kainic acid (KA) into the right STN and, 1-week later, an injection of 6-OHDA in the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Rather, we compared the number of cells in the same nucleus of corresponding sections in different individual cases. This strategy has been used by many recent studies examining issues similar to ours (Piallat et al 1996;Chen et al 2000;Takada et al 2000;Paul et al 2004;Blandini et al 2004). In rats, a statistical comparison of samples was made using the Student's t test (Piallat et al 1996;Blandini et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we compared the number of cells in the same nucleus of corresponding sections in different individual cases. This strategy has been used by many recent studies examining issues similar to ours (Piallat et al 1996;Chen et al 2000;Takada et al 2000;Paul et al 2004;Blandini et al 2004). In rats, a statistical comparison of samples was made using the Student's t test (Piallat et al 1996;Blandini et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, numerous preclinical studies, conducted in rodent and nonhuman primate (NHP) models of PD have demonstrated a beneficial effect of STN lesion or STN‐DBS on SN neuronal survival 8, 12, 13, 14, 15, 16, 17. However, the common drawback of these preclinical studies was the use of toxin‐mediated PD models, either by 1 methyl‐4 phenyl 1,2,3,6‐tetrahydropyridine (MPTP) in NHP14 or 6‐hydroxydopamine (6‐OHDA) in rodents 12, 15, 18, 19.…”
mentioning
confidence: 99%
“…11 In contrast, numerous preclinical studies, conducted in rodent and nonhuman primate (NHP) models of PD have demonstrated a beneficial effect of STN lesion or STN-DBS on SN neuronal survival. 8,[12][13][14][15][16][17] However, the common drawback of these preclinical studies was the use of toxin-mediated PD models, either by 1 methyl-4 phenyl 1,2,3,6-tetrahydropyridine (MPTP) in NHP 14 or 6-hydroxydopamine (6-OHDA) in rodents. 12,15,18,19 These toxin models cause acute nigral lesions and do not adequately reflect the molecular pathology of human PD, specifically they do not exhibit a-synuclein (aSyn)-positive aggregates, a hallmark of PD, and therefore have limited translational value for studying disease-modifying therapies.…”
mentioning
confidence: 99%
“…However, from the results of these studies one cannot conclude that lesioning of the STN conveys nigral neuroprotection in rodent models of PD, as in all studies the STN lesion was initiated one to two weeks prior to 6-OHDA lesion, suggesting a preventive rather than a neuroprotective effect of STN ablation. Additionally, one study also investigated the effect of STN ablation on a preceding 6-OHDA lesion and did not observe attenuation of nigral cell death (35). On the other hand, in the study of Nakao et al (34), a rescue of dopaminergic nigral neurons was only demonstrated in the mitochondrial toxin 3-nitropropionic acid (3-NP)-associated PD model, but not in the 6-OHDA rat model of PD (34).…”
Section: Deep Brain Stimulation and Neuroprotection-lessons From Expementioning
confidence: 98%
“…STN "silencing") should be capable to diminish the deleterious effect of excessive glutamate release on dopaminergic neurons. In this line, in several rodent models of PD, the neuroprotective effects of STN silencing using either neurotoxin induced ablation (33)(34)(35)(36)(37), pharmacological inhibition (38), or phenotypic shift of subthalamic neurons (39) have been investigated. Except for Blandini et al (38), showing an increase of Nissl-labeled nigral cells after chronic NMDA antagonism of the STN, all of these studies showed a partial rescue of tyrosine hydroxylase (TH)-positive cells in the substantia nigra compacta (SNc) following STN silencing (for overview see Table 3).…”
Section: Deep Brain Stimulation and Neuroprotection-lessons From Expementioning
confidence: 99%